Detection and Prevalence of Helicobacter Infection in Pet Cats - Neiger, R. (American Society for Microbiology, 1998)
The presence of spiral bacteria in the feline stomach has been recognized for over a century, but the identities and degrees of prevalence of such organisms in privately owned cats are still poorly documented. The aims of this study were (i) to adapt different diagnostic tools and evaluate their practicality for diagnosing feline gastric Helicobacter colonization, (ii) to determine the prevalence of gastric Helicobacter-like organisms in pet cats, (iii) to identify the feline species, and (iv) to correlate the presence of a Helicobacter infection with gastritis. Biopsy samples were taken gastroscopically from the antra and the corpora of clinically healthy pet cats. Helicobacter-like organisms were detected by Gram staining, Warthin-Starry staining, and rapid urease testing in biopsy specimens and by [(13)C]urea breath testing in 79, 77, 78, and 85% of cases, respectively. PCR analysis revealed that 78% of the cats (38 of 49) were infected by Helicobacter heilmannii; however, none of them was harboring Helicobacter pylori or Helicobacter felis. Culture was positive for one cat; the organism was identified as Helicobacter pametensis by dot blot DNA hybridization. By a combination of the detection methods, 91% of the pet cats were found to be Helicobacter positive. For 46 cats (79%) diagnostic tests were concordant. All cats showed mild to moderate gastritis in either the antrum or the corpus, regardless of the presence or density of gastric bacteria. In summary, pet cats are frequently colonized by H. heilmannii without a significant correlation between infection and degree of gastritis.